The American Senator - Trollope, Anthony, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2004)
"The American Senator" by Anthony Trollope is a novel written in 1877. Set in rural England, it weaves together two romantic pursuits: Mary Masters, a gentlewoman who loves above her station, and Arabella Trefoil, a determined woman who will sacrifice nearly everything to secure a wealthy husband. Meanwhile, American Senator Elias Gotobed observes English society with outsider's eyes, questioning its customs from fox hunting to social hierarchies. Through these intertwined stories, Trollope explores the clash between rationality and tradition in Victorian England. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_American_Senator
Release date is 2004-02-01
E-text prepared by Tapio Riikonen and revised by Joseph E. Loewenstein, M.D.
Keywords: Mate selection -- Fiction; Great Britain -- Social life and customs -- 19th century -- Fiction; Courtship -- Fiction; Political fiction; Americans -- Great Britain -- Fiction; Legislators -- Fiction